TIPOLOGI PERUBAHAN TUTUPAN HUTAN DI KABUPATEN KUBU RAYA KALIMANTAN BARAT - Ikhsani, Hanifah (Fakultas Kehutanan Universitas Lancang Kuning, 2019)
Forest cover changes were influenced by many factors, some of which were biophysical characteristics, socio-economic conditions, and community cultural. The behavior of forest cover changes in each of Indonesia's regions varied, either its rate or its driving factors. The establishment of village typologies to categorize village administrative areas becomes important to see the driving factors that trigger forest change in each typology. The objective of this study was to develop the village typology and to identify the driving forces of forest cover change in each village in Kubu Raya Regency, West Kalimantan. The development of village typology was done by applying the clustering approach with standardized euclidean distances. Based on the proportion of forest in 2015, the study found that there are two village typologies within the study area with 81% OA. The study also recognized that the most significant driving forces of forest cover change in T1 were the distance from rivers (X2) and settlements (X3), whereas in T2 were the distance from roads (X1) and the edge of forest in 2015 (X9). The study concludes that the proximity from the center of the human activities holds a significant influence on the behavior of forest cover changes.